Antiviral Innate Responses Induced by VSV-EBOV Vaccination Contribute to Rapid Protection - Andrea R. Menicucci (American Society for Microbiology, 2019)
ABSTRACT Ebola virus (EBOV) is a single-stranded RNA virus that causes Ebola virus disease (EVD), characterized by excessive inflammation, lymphocyte apoptosis, hemorrhage, and coagulation defects leading to multiorgan failure and shock. Recombinant vesicular stomatitis virus expressing the EBOV glycoprotein (VSV-EBOV), which is highly efficacious against lethal challenge in nonhuman primates, is the only vaccine that successfully completed a phase III clinical trial. Additional studies showed VSV-EBOV provides complete and partial protection to macaques immunized 7 and 3 days before EBOV challenge, respectively. However, the mechanisms by which this live-attenuated vaccine elicits rapid protection are only partially understood. To address this, we carried out a longitudinal transcriptome analysis of host responses in whole-blood samples collected from cynomolgus macaques vaccinated with VSV-EBOV 28, 21, 14, 7, and 3 days before EBOV challenge. Our findings indicate the transcriptional response to the vaccine peaks 7 days following vaccination and contains signatures of both innate antiviral immunity as well as B-cell activation. EBOV challenge 1 week after vaccination resulted in large gene expression changes suggestive of a recall adaptive immune response 14 days postchallenge. Lastly, the timing and magnitude of innate immunity and interferon-stimulated gene expression correlated with viral burden and disease outcome in animals vaccinated 3 days before challenge. IMPORTANCE Ebola virus (EBOV) is the causative agent of Ebola virus disease (EVD), a deadly disease and major public health threat worldwide. A safe and highly efficacious vesicular stomatitis virus-based vaccine against EBOV is the only platform that has successfully completed phase III clinical trials and has been used in recent and ongoing outbreaks. Earlier studies showed that antibodies are the main mode of protection when this vaccine is administered 28 days before EBOV challenge. Recently, we showed this vaccine can provide protection when administered as early as 3 days before challenge and before antibodies are detected. This study seeks to identify the mechanisms of rapid protection, which in turn will pave the way for improved vaccines and therapeutics. Additionally, this study provides insight into host gene expression signatures that could provide early biomarkers to identify infected individuals who are at highest risk of poor outcomes.